Full and Partial Invariance of the Attitudes Structure Scale towards Learning Science Using Confirmatory Factor Analysis: A Comparative Study between Saudi Arabia and Singapore for the Trends in International Mathematics and Science Study (TIMSS) - Jarrah, Bandar Nawaf Tawfieq (Dirasat: Educational Sciences, 2025)
Objectives: The study aims to examine the overall and partial measurement invariance of the attitudes toward science learning scale, which is administered alongside the TIMSS assessment. Methods: The study utilized TIMSS 2019 data from Saudi Arabia and Singapore for a 26-item scale measuring attitudes toward science learning, divided into three dimensions: Love of Science Learning (SLS), Value of Science Learning (SVS), and Confidence in Science Learning (SCS). The Saudi sample included 1,945 male and 1,927 female students, while the Singaporean sample included 2,451 male and 2,343 female students. Multi-group confirmatory factor analysis (MGCFA) was used for data analysis. Results: The findings revealed that measurement invariance was not achieved for female data between Saudi Arabia and Singapore. Partial measurement invariance was found for male data, with significant differences favoring Saudi males in the Love of Science Learning (SLS) and Value of Science Learning (SVS) dimensions, while no differences were observed in Confidence in Science Learning (SCS). Complete measurement invariance was achieved within Saudi Arabia for male and female data, with no significant differences between them. In Singapore, partial measurement invariance was achieved between males and females, with significant differences across all three dimensions (SLS, SCS, and SVS), favoring males. Conclusion: Complete invariance was achieved within Saudi Arabia between males and females, while partial invariance was observed in Singapore and between male data across both countries. Invariance was not achieved for female data across countries. The study recommends further research on invariance across countries and years.